Cortical excitability and neuropsychological functioning in healthy adults. (28th July 2017) - Bolden, Lauren B.; Griffis, Joseph C.; Pati, Sandipan; Szaflarski, Jerzy P.
Abstract: Evidence from clinical populations, such as epilepsy and attention deficit/hyperactivity disorder, suggests a relationship between hyperexcitability and cognitive impairment, but this relationship has not been demonstrated in healthy individuals. Here, we investigate the relationship between cortical excitability and cognitive functioning in healthy adults. Single- and paired-pulse TMS was applied to 20 healthy adults to measure cortical excitability and long-interval intracortical inhibition (LICI). A neuropsychological battery was administered to assess aspects of attention, executive function, and mood. Participants with primarily excitatory responses to the LICI paradigm performed worse on a composite measure of attention and reported more negative mood states than participants with primarily inhibitory responses. Thus, differences in attention and mood among healthy adults are related to differences in cortical excitability as measured by LICI. This is consistent with a role for GABAB inhibitory circuits in regulating attention and mood, and suggests that individual variability in these domains may reflect variability in cortical excitability. This study demonstrates preliminary evidence that increased cortical excitability is associated with poorer cognition and mood in healthy adults. These findings provide new insight into the presence of cognitive dysfunction in several patient populations with hyperexcitability and support the development of neurostimulation interventions for clinical use. Highlights: There is a relationship between excitability and cognition in healthy adults. Motor cortex hyperexcitability is associated with attention deficits. Motor cortex hyperexcitability is associated with poorer mood.